Understanding Climate Change through Farmers, Meteorogical Evidence, and Rapeseed Yield under Staggered Planting Dates in Tikapur, Kailali - Pandit, Samikshya; Amgain, Lal Prasad; Khanal, Subodh (Journal of Agriculture and Forestry University, 2025)
Climate change poses a serious challenge to agriculture-dependent regions such as the western Terai of Nepal. This study assessed farmers’ perceptions of climate change, analyzed long-term climatic trends, and evaluated the performance of rapeseed (Brassica campestris L. var. toria) under different sowing dates in Tikapur Municipality, Kailali. Household surveys documented farmers’ experiences and adaptation practices, while historical meteorological data (1990–2020) were analyzed using the non-parametric Mann–Kendall test. Farmer-managed on-farm experiments were conducted to compare rapeseed yield across three sowing dates. More than 81% of farmers perceived increasing summer temperatures, shorter and warmer winters, and more erratic and declining rainfall. Climatic analysis confirmed decreasing trends in annual, monsoon, and winter rainfall by 3.52, 2.92, and 0.65 mm yr⁻¹, respectively, along with an increasing trend in summer maximum temperature. Summer minimum temperature declined by 0.014–0.029 °C yr⁻¹, while winter minimum and maximum temperatures showed mixed trends. Field results showed significant yield differences among sowing dates, with the highest yield obtained from crops sown in the first fortnight of Ashwin. Overall, adjusting sowing dates emerged as an effective and practical climate adaptation strategy for rapeseed production in the western Terai.